2012
DOI: 10.1590/s1516-14392012005000012
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior and physical characterization of surface-modified Ti-6Al-4V ELI alloy by micro-arc oxidation

Abstract: Anodizing has proven an effective method for preparing bioactive titanium and has been the subject of many studies regarding the performance and biological characterization of the layers obtained. However, the fatigue behavior of titanium alloys, after undergoing this process is still poorly studied. This study aims to investigate the influence of MAO (Micro-Arc Oxidation) process on the fatigue properties of titanium alloy Ti-6Al-4V. Therefore axial fatigue tests were performed to obtain SxN curves, of specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is important to mention that these fatigue data were all obtained using exactly the same experimental conditions, such as axial loading, stress ratio R = 0.1 and frequency in the range of 5-20 Hz. Micro-arc oxidation 12 and chemical etching 3 produced modified layers with R z value smaller than the critical R z in the curve of Figure 5, and therefore the fatigue strength The boundary conditions and the methodology are published elsewhere 17 . The calculations show that values in the range of ~400 MPa to 650 MPa can be obtained in critical parts of the stem and would induce fatigue cracks before the limit of 5x10 6 cycles established by the biomedical standards for such components.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that these fatigue data were all obtained using exactly the same experimental conditions, such as axial loading, stress ratio R = 0.1 and frequency in the range of 5-20 Hz. Micro-arc oxidation 12 and chemical etching 3 produced modified layers with R z value smaller than the critical R z in the curve of Figure 5, and therefore the fatigue strength The boundary conditions and the methodology are published elsewhere 17 . The calculations show that values in the range of ~400 MPa to 650 MPa can be obtained in critical parts of the stem and would induce fatigue cracks before the limit of 5x10 6 cycles established by the biomedical standards for such components.…”
Section: Discussionmentioning
confidence: 99%
“…There are certainly reports [96100] of significant impairment of fatigue life, for both Al and Mg alloys. There have been very few indications of any improvement, although it has been reported [101] that no change occurs with the Ti–6Al–4V alloy. It is thus certainly an area of concern.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Other studies have been noted where a decrease in fatigue life was reported for other Al and Mg alloys [ 178 , 179 , 180 ]. However, for the PEO process carried out on Ti 6 Al 4 V alloy, no change in fatigue life occurred [ 181 ]. After completion of the PEO process, residual electrolytes remained in the coating.…”
Section: Mechanical Attributes Of Peo Coatingsmentioning
confidence: 99%